LINTASAN BELAJAR SISWA DALAM MEMAHAMI SISTEM PERSAMAAN LINIER DUA VARIABEL MELALUI PROBLEM BASED LEARNING - Binti Ir Zulkarnain, Ayu Najmita; Zulfah Marpaung; Ellis Mardiana Panggabean; Tua Halomoan Harahap (Najah Bestari, 2025)
This study is motivated cause many students face challenges does not understand two variable linear equation system (SPLDV), primarily due to the abstract nature of the concepts. These difficulties hinder their ability to solve real-world problems effectively. Addressing these issues requires a structured instructional approach that supports students' learning processes. This study aims to analyze the learning trajectory of students in understanding two variable linear equation system (SPLDV through a Problem-Based Learning (PBL) approach. The research identifies specific stages of student learning, including basic concept comprehension, problem modeling, problem-solving, and applying solutions to real-world contexts. Data were collected through classroom observations, analysis of instructional materials, and interviews with eighth-grade students. The findings highlight that PBL not only enhances students' engagement but also helps develop critical and analytical thinking skills. This study underscores the importance of designing problem-based instructional materials to address learning challenges and recommends further exploration of PBL applications in mathematics education. .